HUBUNGAN ANTARA MEROKOK DENGAN PENYAKIT PARKINSON DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Setyono, Joko; Noviani, Erni; Gunarto, Untung (MANDALA of Health, 2010)
Cigarettes contain 2,3,6-trimethyl-4-napthoquinone which can inhibit the breakdown of dopamine;therefore, smoking can reduce the risk of Parkinsonâs disease. On the other hand, smoking is the secondcause of death in the world. This study was aimed to investigate the relationship between smoking status,smoking duration, smoking quantity, types of cigarettes and Parkinsonâs disease. This study was ananalytical observational research using case control approach that involved 34 patients of Parkinsonâsdisease as a case group and 34 respondents that were non Parkinson as a control group. The former and thelater were age- and sex-matched control subjects selected by using purposive sampling technique. InParkinson group it was obtained that as much as 64.7% of the respondents were non smokers, 14.7% wereformer smokers, 8.8% were current less than daily smokers, and 8.8% were current daily smokers. In nonParkinson group, 41.2% of the respondents were non smokers, 23.5% were former smokers, 8.8% werecurrent less than daily smokers, and 26.5% were current daily smokers. The data were analyzed usingWilcoxon test and it was found that there was a significantly negative relationship between smoking status,smoking duration, smoking quantity, types of cigarettes and Parkinsonâs disease (p<0,05). There was asignificantly negative relationship between smoking status, smoking duration, smoking quantity, types ofcigarettes and Parkinsonâs disease.